2009
DOI: 10.1186/1471-2180-9-27
|View full text |Cite
|
Sign up to set email alerts
|

In vivo killing of Staphylococcus aureus using a light-activated antimicrobial agent

Abstract: BackgroundThe widespread problem of antibiotic resistance in pathogens such as Staphylococcus aureus has prompted the search for new antimicrobial approaches. In this study we report for the first time the use of a light-activated antimicrobial agent, methylene blue, to kill an epidemic methicillin-resistant Staphylococcus aureus (EMRSA-16) strain in two mouse wound models.ResultsFollowing irradiation of wounds with 360 J/cm2 of laser light (670 nm) in the presence of 100 μg/ml of methylene blue, a 25-fold red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
110
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(125 citation statements)
references
References 29 publications
3
110
0
2
Order By: Relevance
“…25,26 Much is already known about the photodynamic inactivation of microorganisms: both antibiotic-sensitive and -resistant strains can be successfully photoinactivated, and there is the additional advantage that repeated photosensitization of bacterial cells does not induce a selection of resistant strains. [27][28][29][30] In our previous study, we investigated the photodynamic activity of a new photosensitive (sinoporphyrin sodium [DVDMS]). We observed that light-activated DVDMS enhanced intracellular ROS levels, which significantly induced cell death and markedly damaged S. aureus.…”
mentioning
confidence: 99%
“…25,26 Much is already known about the photodynamic inactivation of microorganisms: both antibiotic-sensitive and -resistant strains can be successfully photoinactivated, and there is the additional advantage that repeated photosensitization of bacterial cells does not induce a selection of resistant strains. [27][28][29][30] In our previous study, we investigated the photodynamic activity of a new photosensitive (sinoporphyrin sodium [DVDMS]). We observed that light-activated DVDMS enhanced intracellular ROS levels, which significantly induced cell death and markedly damaged S. aureus.…”
mentioning
confidence: 99%
“…Zolfaghari et al 17 evaluated the in vivo effect of PDT in mice with excisional and superficial skin wounds inoculated with a suspension of MRSA. The wounds were treated with 0.3 µM MB and irradiated with 360 J/cm² of diode laser light for 30 min.…”
mentioning
confidence: 99%
“…We have to take into account that photoinactivation is able to eradicate microorganisms without discriminating resistant isolates, both planktonic and biofilm species. This is in concert with the potential of localized photooxidative stress to inactivate virulence factors 134,135 and virulence determinants [136][137][138] in the absence of any documented conventional resistance mechanism. The possibility of active efflux seems to be related with some but not all the molecular classes of PSs although improved delivery methods may overcome this barrier.…”
Section: Biofilm Eradicationmentioning
confidence: 96%